Catalyst Asia Issue 02 - Institute for Societal Leadership (Institutional Knowledge at Singapore Management University, 2015)
STORIES FROM THE GROUND Food Aid, Powered By Technology Myanmar’s Microfinance Leader Says Rules Are Too Tight Empowering The Disenfranchised Kitchen On A Mission A Year On, Somaly Mam Scandal Still Raises Questions Dili 360° Closing The Accessibility Gap Pattern Recognition It Takes A Village To Raise Haiyan’s Children For The Love Of Gems – A Photo Story From The Streets Of Jakarta Philanthropists And Trust In Mainland China The American Known In North Korea IN THE HOT SEAT Bridging Two Worlds Through Conversation The Gift Of Sight Seeing With New Eyes Sarus – Hope Is The Thing With Feathers PERSPECTIVES FROM THE TOP Leading Authentically – Overcoming The ‘Mind-boggling’ Consequences Of Mindless Leadership Education Systems Can Get Better What Value Design? Growing Into Inertia